Solve this
Question:

$3 \sqrt{7} x^{2}+4 x-\sqrt{7}=0$

 

Solution:

Given:

$3 \sqrt{7} x^{2}+4 x-\sqrt{7}=0$

$\Rightarrow 3 \sqrt{7} x^{2}+7 x-3 x-\sqrt{7}=0$

$\Rightarrow \sqrt{7} x(3 x+\sqrt{7})-1(3 x+\sqrt{7})=0$

$\Rightarrow(3 x+\sqrt{7})(\sqrt{7} x-1)=0$

$\Rightarrow 3 x+\sqrt{7}=0$ or $\sqrt{7} x-1=0$

$\Rightarrow x=\frac{-\sqrt{7}}{3}$ or $x=\frac{1}{\sqrt{7}}=\frac{1 \times \sqrt{7}}{\sqrt{7} \times \sqrt{7}}=\frac{\sqrt{7}}{7}$

Hence, the roots of the equation are $\frac{-\sqrt{7}}{3}$ and $\frac{\sqrt{7}}{7}$.

 

Administrator

Leave a comment

Please enter comment.
Please enter your name.